Interactive directory based on touch-screen panel ii - Lim, Ting Han. (2010)
With the many professors who teach in the School of EEE, come hundreds of their offices located throughout the buildings of EEE. This results in many students, even after a few years in the school, having a need to check the offices of different professors when the need arises. This is more evident for first time visitors to the school, and with the offices on different levels in different buildings, directions to the offices is not an easy task.